Analizando videos de TikTok de la campaña de vacunación contra la COVID-19 desde cuentas del sector salud - Pichihua, Sofía Pamela (2024)
TikTok’s popularity in Peru during the COVID-19 pandemic confirmed that public entities linked to the health sector such as the Ministry of Health and EsSalud must define an active digital communication strategy. This research describes which characteristics of COVID-19 vaccination campaign videos in those accounts were the most effective in going viral. In conclusion of content analysis, short videos with at least one hashtag usually get more interaction and views; while dance challenges and newstype videos were frequently used by both accounts. The popularity of the videos also responds to the participation of health personnel and the immunized population. This research also provides a guide for TikTok’s narrative videos related to the public health context.